Associative factors for atopic dermatitis and other atopic diseases in middle-aged adults : A population-based birth cohort study among 5373 subjects - Haarala, Anna K. K.; Sinikumpu, Suvi-Päivikki; Jokelainen, Jari; Pekkanen, Juha; Huilaja, Laura (Health Science Reports, 2023)
Background and aimsThe study aimed to examine parental, longitudinal and current associative factors for atopic dermatitis (AD) and to compare those to other atopic diseases in 46-year-old adults. MethodsQuestionnaire data from the Northern Finland Birth Cohort 1966 study were used. To analyze allergic sensitization, skin prick tests (n = 5373) were performed for birch, timothy, cat, and house dust mite at age 46. ResultsMaternal (odds ratio [OR] 1.81; 95% confidence interval [CI] 1.25-2.59) and paternal allergy (OR 2.54; CI 1.76-3.64), sensitization to any of the four tested aeroallergens (OR 1.56; CI 1.04-2.30) as well as polysensitization (OR 3.04; CI 2.10-4.37) were associated with current AD. Living on a farm in infancy was negatively associated with allergic rhinitis, allergic conjunctivitis, and atopic multimorbidity. Current AD (OR 2.65; CI 1.44-4.60) and all atopic diseases associated with indoor air related symptoms. Current AD associated with other atopic diseases, most strongly with allergic rhinitis (OR 4.92; CI 3.92-6.22). ConclusionCurrent AD in a 46-year-old general population occurred frequently with allergic rhinitis, allergic conjunctivitis, and asthma in the Northern Finland Birth Cohort study 1966. Parental allergy and sensitization to common aeroallergens were found as shared associative factors for AD, allergic rhinitis, allergic conjunctivitis, and asthma. AD and other atopic diseases associated with symptoms related to poor indoor air quality. In daily practice, it is important to take these comorbidities into consideration when treating patients with AD. Peer reviewed